Bi-Modal Arterial Compliance Probe for Calibration-Free Cuffless Blood Pressure Estimation - Nabeel, P. M.; Jayaraj, Joseph; Srinivasa, Karthik; Mohanasankar, Sivaprakasam; Chenniappan, M. (IEEE transactions on biomedical engineering, 2018)
Objective: We propose a calibration-free method and system for cuffless blood pressure (BP) measurement from superficial arteries. A prototype device with bi-modal probe arrangement was designed and developed to estimate carotid BP - an indicator of central aortic pressure. Methods: Mathematical models relating BP parameters of an arterial segment to its dimensions and local pulse wave velocity (PWV) are introduced. A bi-modal probe utilizing ultrasound and photoplethysmograph sensors was developed and used to measure diameter values and local PWV from the carotid artery. Carotid BP was estimated using the measured physiological parameters without any subject- or population-specific calibration procedures. The proposed cuffless BP estimation method and system were tested for accuracy, usability, and for potential utility in hypertension screening, on a total of 83 subjects. Results: The prototype device demonstrated its capability of detecting beat-by-beat arterial dimensions and local PWV simultaneously. Carotid diastolic BP (DBP) and systolic BP (SBP) were estimated over multiple cardiac cycles in real-time. The absolute error in carotid DBP was <;10 mmHg in 82% cases, and root-mean-square-error = 8.3 mmHg. Consistent with the theory, estimated SBP at the carotid site was lower than the reference brachial SBP. ROC curves obtained for hypertension screening analysis revealed an area under the curve ≥0.8 for both carotid SBP and DBP values, illustrating the potential for using the developed method in hypertension screening. Conclusion: The feasibility of calibration-free, cuffless BP measurement at an arterial site of interest was demonstrated with a level of acceptable accuracy. The study also demonstrated the potential utility of the proposed method and system in hypertension screening and local evaluation of arterial stiffness indices. Significance: Novel approach for calibration-free cuffless BP estimation; a potential tool for local BP measurement and hypertension screening.